2013
DOI: 10.1016/j.tem.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine and bone metabolism

Abstract: Bone is a dynamic organ that undergoes continuous remodeling whilst maintaining a balance between bone formation and resorption. Osteoblasts, which synthesize and mineralize new bone, and osteoclasts, the cells that resorb bone, act in concert to maintain bone homeostasis. In recent years, there has been increasing appreciation of purinergic regulation of bone metabolism. Adenosine, released locally, mediates its physiologic and pharmacologic actions via interactions with G-protein coupled receptors and recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 74 publications
2
130
0
Order By: Relevance
“…Here we describe, for the first time, a direct effect of A2AR activation on bone regeneration in vivo, either via direct activation of the receptor or by enhancing extracellular adenosine levels by blockade of Ent1 transporter. Previously, we reported that activation of the A2AR inhibits osteoclast differentiation (17)(18)(19) both in vitro and . Immunohistochemistry for markers of bone remodeling.…”
Section: Discussionmentioning
confidence: 98%
“…Here we describe, for the first time, a direct effect of A2AR activation on bone regeneration in vivo, either via direct activation of the receptor or by enhancing extracellular adenosine levels by blockade of Ent1 transporter. Previously, we reported that activation of the A2AR inhibits osteoclast differentiation (17)(18)(19) both in vitro and . Immunohistochemistry for markers of bone remodeling.…”
Section: Discussionmentioning
confidence: 98%
“…Repair of the skeletal system depends on the differentiation of osteoblasts from their progenitors (mesenchymal stem cells, MSCs) which have a broad, multilineage differentiation potential and express A1, A2A, A2B, and A3 receptors [67,68] (see Fig. 3).…”
Section: Regulation Of Osteoblast Differentiation and Function By Adementioning
confidence: 99%
“…When bones are damaged, increased extracellular ATP produces adenosine, a purine nucleoside produced in response to low-oxygen and inflammatory stimuli (Mediero and Cronstein, 2013;Bowler et al, 2001;Orriss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine binds to four adenosine receptors (A1R, A2AR, A2BAR and A3R) that are members of the G proteincoupled receptor family for the specific actions (Mediero and Cronstein, 2013;Bowler et al, 2001;Orriss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation